Diagnosis and management of supernumerary teeth in Pediatric Dentistry – Case report (Research, Society and Development, 2023)
This study aimed to explore the etiology, diagnosis, prevalence and treatment of supernumerary teeth, based on current scientific evidence. Presenting a case report of a child patient at the Dental Clinic of Universidade Tiradentes-UNIT, whose legal guardian complained of dissatisfaction due to the presence of an “extra tooth”. After clinical and radiographic diagnosis, the presence of a supernumerary tooth was confirmed. The treatment involved the surgical removal of this tooth, the surgery was performed using a closed surgical technique. This removal of supernumerary teeth in children aims to prevent potential aesthetic and functional disorders associated with the pathology, while taking advantage of a favorable prognosis at a young age.